The Emperor's New Clothes: PRospective Observational Evaluation of the Association Between Initial VancomycIn Exposure and Failure Rates Among ADult HospitalizEd Patients With Methicillin-resistant Staphylococcus aureus Bloodstream Infections (PROVIDE). (3rd June 2019) - Lodise, Thomas P; Rosenkranz, Susan L; Finnemeyer, Matthew; Evans, Scott; Sims, Matthew; Zervos, Marcus J; Creech, C Buddy; Patel, Pratish C; Keefer, Michael; Riska, Paul; Silveira, Fernanda P; Scheetz, Marc; et al.
Abstract: Background: Vancomycin is the most commonly administered antibiotic in hospitalized patients, but optimal exposure targets remain controversial. To clarify the therapeutic exposure range, this study evaluated the association between vancomycin exposure and outcomes in patients with methicillin-resistant Staphylococcus aureus (MRSA) bacteremia. Methods: This was a prospective, multicenter (n = 14), observational study of 265 hospitalized adults with MRSA bacteremia treated with vancomycin. The primary outcome was treatment failure (TF), defined as 30-day mortality or persistent bacteremia ≥7 days. Secondary outcomes included acute kidney injury (AKI). The study was powered to compare TF between patients who achieved or did not achieve day 2 area under the curve to minimum inhibitory concentration (AUC/MIC) thresholds previously found to be associated with lower incidences of TF. The thresholds, analyzed separately as co-primary endpoints, were AUC/MIC by broth microdilution ≥650 and AUC/MIC by Etest ≥320. Results: Treatment failure and AKI occurred in 18% and 26% of patients, respectively. Achievement of the prespecified day 2 AUC/MIC thresholds was not associated with less TF. Alternative day 2 AUC/MIC thresholds associated with lower TF risks were not identified. A relationship between the day 2 AUC and AKI was observed. Patients with day 2 AUC ≤515 experienced the best global outcomes (no TF and no AKI). Conclusions: Higher vancomycin exposures did not confer a lower TF risk but were associated with more AKI. The findings suggest that vancomycin dosing should be guided by the AUC and day 2 AUCs should be ≤515. As few patients had day 2 AUCs <400, further study is needed to define the lower bound of the therapeutic range. Abstract : A multicenter prospective study was performed to evaluate the relationship between day 2 vancomycin exposure profiles and outcomes in patients with methicillin-resistant Staphylococcus aureus bacteremia. The collective findings suggest that vancomycin dosing should be guided by the area under the curve (AUC) and day 2 AUCs should be maintained between 400 and 515.